Controlled Growth of Vertically Oriented Trilayer MoS2 Nanoflakes for Room‐Temperature NO2 Gas Sensor Applications. Issue 12 (29th April 2020) - Hung, Chu Manh; Vuong, Vy Anh; Duy, Nguyen Van; An, Dinh Van; Hieu, Nguyen Van; Kashif, Muhammad; Hoa, Nguyen Duc
Abstract : The controlled synthesis of few‐layer vertically oriented MoS2 flakes for high‐performance NO2 gas sensor applications is introduced. The density and the thickness of MoS2 nanosheets are controlled by varying the heating rate of the chemical vapor deposition process. Herein, it is confirmed that the nanoflakes of about three layers are obtained under the heating rate of 5 °C using powders of MoO3 and S as precursors without using any catalyst. This is very advantageous because no catalyst is used, there is no need of buffer layer at the bottom of the MoS2 thin‐film flacks, thus omitting the leakage current when measuring the electrical signal and enhancing the gas sensing performance. Gas sensing measurements demonstrate that the interconnected vertically oriented MoS2 nanoflakes have a good response value of 20.1% to 0.5 ppm NO2 at room‐temperature (RT), and 1.73% at 150 °C. The sensor shows full recovery characteristic at a measured temperature of 150 °C with response and recovery time of about 15 and 100 s, respectively. The sensor also exhibits good selectivity with the ignorable response to SO2, H2, NH3, H2 S, and a low detection limit of 42 ppb. Abstract : Without the use of any buffer layer, vertically oriented trilayer MoS2 nanoflakes are grown on‐chip by chemical vapor deposition method for room‐temperature NO2 gas sensor application. Taking advantages of the vertically aligned nanoflakes, the NO2 gas is adsorbed on both sides of the nanoflakes, thus significantly enhancing the gas sensing performance of the sensor.